Kepemimpinan Transformasional, Kepercayaan dan Berbagi Pengetahuan dalam Organisasi - Avin Fadilla Helmi; Iman Arisudana (Faculty of Psychology, Universitas Gadjah Mada, 2009)
Many research in knowledge sharing has focused their attention on the roles of information and technology factor. Recently, there is a consideration that human factors such as social interaction, trust and leadership play keyrole in knowledge sharing behavior. This study aimed to investigate the factors affecting employeesʹ knowledge sharing within an organization by combining transformational leadership and trust as predictor of knowledge sharing behavior. This research used survey method, and take 99 employees of PT. Bina Karya Jakarta as sample. The instruments to get data was questionnaire of Likert’s Scale, that consisted of leadership scale, organizational trust scale, managerial trust, co‐worker trust scale and knowledge sharing scale. The research found that transformational leadership, organizational trust, management trust and co‐worker trust together have significant effect on knowledge sharing behavior with r=0,264. The regression coefficient also shows there is only the co‐worker trust that have the most significant effect on knowledge sharing behavior. These findings need to be discussed for further research especially to gain understanding about the role transformational leadership and trust on knowledge sharing that vary, depends on the situation and condition.